The association of dietary behaviors and practices with overweight and obesity parameters among Saudi university students - Syed, Nabeel Kashan; Syed, Mamoon Hussain; Meraya, Abdulkarim M.; Albarraq, Ahmed A.; Al-kasim, Mohamed Ahmed; Alqahtani, Saad; Makeen, Hafiz Antar; Yasmeen, Ayesha; Banji, Otilia J. F.; Elnaem, Mohamed Hassan Abdelaziz (PLOS, 2020)
Western dietary habits, coupled with a sedentary lifestyle, are potential contributors to the prevalence and rapid increase in the incidence of obesity in Saudi Arabia. This study aimed to investigate the association between students’ weight status and their eating behaviors and practices. Another aim was to assess students’ awareness of the health risks associated with obesity. Methods A cross-sectional survey was conducted among a sample of 416 (53% male and 47% female) undergraduate students, aged 18–26 years old, between January 6 and April 6, 2019, from colleges of Health Sciences at Jazan University in the Kingdom of Saudi Arabia (K.S.A). Students completed a self-administered questionnaire and recorded their measured anthropometric parameters. Results The prevalence of overweight (20.4%) and obesity (14.9%) were relatively high among the participants. There were statistically significant associations between Body Mass Index (BMI) and the different settings of food consumption (i.e., dining on a table (or) in the Islamic way: squatting on the ground) (p<0.001)). BMI was also associated with students’ dietary habits regarding consuming food, snacks, and drinking carbonated beverages while watching television (p<0.001), as well as consuming the same pattern of food/drink while watching television, playing video games on mobile phones or computers (p<0.001). Nearly most of the students were oblivious to the fact that metabolic syndrome, reproductive disorders, respiratory disorders along with liver and gallbladder diseases are some of the health risks associated with obesity. Conclusion The prevalence of obesity and overweight were reasonably high in our study sample and were affected by several factors related to students’ eating behaviors and practices. This warrants the need for rigorous and frequent health education interventions on healthy eating behaviors, dietary practices, with an emphasis on the importance of adopting an active, healthy lifestyle.